Bioactive natural compounds as potential medications for osteogenic effects in a molecular docking approach - Wu, Yuqiong; Liu, Yulan; Xu, Yuanjin; Zheng, Ao; Du, Jiahui; Cao, Lingyan; Shi, Junfeng; Jiang, Xinquan (Frontiers in Pharmacology, 2022)
Bone defect repair and fracture healing are critical challenges in clinical treatments. Bioactive natural compounds are potential resources for the medications on osteogenic effects. We have identified icariin, the effective constituent of Epimedium pubescens, to promote osteogenic differentiation of bone mesenchymal stem cells (BMSCs) and repair bone defects. To explore more natural compounds with the potential modality for bone repair, in the present study, we employed icariin-induced gene expression pattern as an osteogenic model, and screened CMap database for small molecules with similar gene expression signatures to this model. We verified the effectiveness of this molecule docking approach by introducing hydroxycholesterol, the second highest score of the similarity to icariin, into the osteoinductive experiments in vitro, and demonstrated its excellent osteogenic effect on BMSCs compared with a BMP-2 positive control group. Based on the compatible result of hydroxycholesterol, subsequently, Ginsenoside Rb1 was chosen as a most drug-like natural compound among the molecule docking results from icariin. Finally, Ginsenoside Rb1 was demonstrated to promote the expression of osteoblastic genes and ALP activity in vitro, as well as repair the calvarial defect of rats in vivo. The study aims to provide diverse choices for clinical application on bone repair and functional regeneration.